2014
DOI: 10.21608/jpp.2014.64848
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variance Revealed in Cowpea by Partial Diallel and Factorial Mating Designs

Abstract: Genetic variability and heritability are two important factors for plant improvement programs where the magnificence and type of this variability determine the selection criteria to be used by the breeder. This study aimed to estimate the genetic components associated with variance and covariance based on partial diallel crosses and factorial mating designs, as well as, to identify the association between yield components and other quantitative traits to extend an orientation for selection. Six cowpea varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The high narrow sense heritability for 100 seeds weight reported in this study is in agreement with the findings of previous studies where medium to high narrow sense heritability effects were reported (Lopes et al, 2003;Idahosa et al, 2010;Tignegre, 2010;Egbadzor et al, 2013;Ameen et al, 2014). However, predominant non-additive effects indicating low heritability was also reported for this character (Raut et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The high narrow sense heritability for 100 seeds weight reported in this study is in agreement with the findings of previous studies where medium to high narrow sense heritability effects were reported (Lopes et al, 2003;Idahosa et al, 2010;Tignegre, 2010;Egbadzor et al, 2013;Ameen et al, 2014). However, predominant non-additive effects indicating low heritability was also reported for this character (Raut et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Similar finding was reported by Ameen et al (2014), who found higher values of broad-sense and narrow-sense heritability indicating good genetic variability for effective selection in cowpea. High heritability value for 100-seed weight, vegetable pod yield and pod weight were reported by Resmi (1998) and Thiyagarajana (1989).…”
Section: The Diallel Analysis Of Variancesupporting
confidence: 89%
“…The dominance variance (H 1 ) was higher than the additive variance (D) for all traits except TF, WP, WS and TS, these results are in agreement with Mohamed et al (2015). The results illustrated that diallel crosses appeared the relative magnitudes of mean squares for GCA variances in F 1 hybrids and F 2 generations which were larger than those of SCA for all traits in cowpea (Ameen et al, 2014). Supriyo et al (2010) reported that the magnitude of nonadditive gene effect was higher than that of additive gene effect for each studied trait in black gram.…”
Section: The Diallel Analysis Of Variancementioning
confidence: 84%